(untitled) (The Journal of Psychology and Sociology, 2025)
The problem of school engagement among adolescents has gained particular relevance in recent years due to its importance for academic success, psychological well-being, and social adaptation of students. The purpose of this study was to identify the predictors of school engagement and disengagement among senior adolescents, with a focus on the role of academic motivation, bases of self-esteem, and responsibility as components of self-regulation. The empirical research was conducted on a sample of 286 adolescents in grades 8–11 (142 boys and 144 girls). The methodological toolkit included the Brief Academic Motivation Scale (Gordeeva, Sychev, Osin, 2012), the Questionnaire of Bases of Adolescents’ Self-esteem (Lunkina, Gordeeva, 2019), the Multidimensional School Engagement Scale (Wang et al., 2019; adapted by Fomina & Morosanova, 2020), and the Responsibility in Adolescents Scale (Danilova et al., 2024). Data processing was carried out using structural equation modeling (SEM) in SPSS 27. The results showed that adolescents’ engagement is primarily determined by personal and social resources (responsibility, self-control, support), whereas academic motivation has a limited impact. In contrast, disengagement is largely explained by motivational determinants: external motivation, compensatory self-esteem, and avoidance of responsibility. Thus, motivation plays a greater role in preventing school disengagement than in fostering active engagement. The value of the study lies in clarifying the predictors of school engagement and disengagement among senior adolescents and in confirming the relative independence of these constructs. The practical significance of the work consists in the possibility of developing targeted psychological and educational programs aimed at reducing disengagement and strengthening the personal resources of engagement. Key words: school engagement, disengagement, academic motivation, self-esteem, responsibility.